Spatiotemporal variation of the epifaunal assemblages associated to Sargassum muticum on the NW Atlantic coast of Morocco - Belattmania, Zahira (2020)
Epifaunal assemblages inhabiting the non-indigenous macroalga Sargassum muticum (Yendo) Fensholt were investigated on two physically distinct intertidal rocky (S1) and sandy (S2) sites along the Atlantic coast of Morocco. The objective of this study was to test whether the habitat-forming marine alga S. muticum invasive in these sites supported different epifaunal assemblages under different environmental conditions and through time. The gastropods Steromphala umbilicalis, S. pennanti, and Rissoa parva and the isopod Dynamene bidentata were the most contributive species to the dissimilarity of epifaunal assemblage structure between both sites throughout seasons. SIMPER analysis showed a dissimilarity of 58.3-78.5% in the associated species composition of S. muticum between study sites with respect to sampling season. Species diversity and total abundance were significantly higher at the rocky site compared to the sandy site. PERMANOVA analyses showed significant differences of associated epifaunal assemblage structure for the season and site interaction. Accordingly, site and season were determinant factors conditioning the role of habitat in structuring epifaunal assemblages.